Comparative Social Media Analysis on Air Pollution Awareness in Macedonia - Stojcheva, Marija; Dedinec, Aleksandra; Prodanova, Jana; Sandev, Trifce; Wu, Desheng; Kocarev, Ljupco (My University, 2024)
Air pollution is a significant problem in cities and urban centers in Macedonia, impacting both the environment and public health. This study aims to investigate the evolution of public awareness regarding air pollution in Macedonia over the past three years, with a focus on discussions on social media platform X (Twitter). Recognizing social media platforms as influential channels for disseminating information and raising awareness, the correlation between tweets and PM10 particles is explored. Utilizing natural language processing techniques, specifically sentiment analysis and topic modeling, alongside statistical methods such as correlation analysis and Kruskal–Wallis H test, the study examines public sentiment and trending topics associated with air pollution. In addition to providing insight into public perceptions of air pollution, the results assist in determining if public awareness has increased from previous years.
Keywords: air pollution, pm10, natural language processing, sentiment analysis, topic modeling, correlation analysis, Kruskal–Wallis H test, social media platforms, X analysis, Twitter